Multimedia quality evaluation model in streaming service environments - Koo, Ja Ok; Choi, Young June; Li, Zhetao; Pei, Tingrui; Jembre, Yalew Zelalem (International Journal of Ad Hoc and Ubiquitous Computing, 2020)
Recently, mobile broadcast services such as digital media broadcasting (DMB) have generated a rapid increase in multimedia services via the internet compared to traditional cable or satellite delivery. Multimedia via the internet is consumed under different network conditions and through various devices. In this study, we propose a multimedia quality measurement model to assess quality consumes perspective. First, we select the parameters that affect the quality of multimedia at both the application and network levels, and then use these parameters to produce multiple altered versions of an original video. For each video and device, participants provide a mean opinion score (MOS). After determining the effect of parameters on videos and devices. Multiple regression on the MOS dataset collected from the subjects is applied to devise a model called MOS multimedia streaming (MOSMS). Finally, dividing the collected data as a training set and a test set, we validate the new model.
Keywords: Effect of parameters; Mean opinion scores; Mobile broadcast services; Multimedia quality; Multimedia streaming; Multiple regressions; Network condition; Streaming service; Mean opinion score; Mobile devices; MOS; Multimedia; Quality assessment; Streaming services